تجزئة وقياس منطقة الرأس في الصور فوق الصوتية للجنين بشكل آلي - ساعي مريم; إبراهيم عيسى; قريطم زيد (Latakia University Journal -Engineering Sciences Series, 2017)
يقدم البحث طريقة مبتكرة في تجزئة رأس الجنين آلياً في الصور فوق الصوتية Ultrasound Images قليلة التباين. حيث تعاني تلك الصور من كمية ضجيج مرتفعة تؤثّر على الظهور البصري لمنطقة الرأس, كذلك ضعف الحواف وعدم إحاطتها بالمنطقة المرغوبة بشكل كامل يجعل من عملية التجزئة صعبة ومهمة في نفس الوقت, خصوصاً أن البحث اعتمد التجزئة الآلية Auto Segmentation دون الحاجة إلى تدخل المستخدم في أي مرحلة من المراحل. اعتمدنا على تقنية ضبط المستوى Level-Set لتجزئة منطقة الرأس, بعد تحديد الإطار الأولي Initial Contour بشكل آلي عن طريق تابع خصائص المنطقة Region Properties. الطريقة المقترحة أثبتت فعاليتها في اقتطاع منطقة الرأس دون التأثّر بالضجيج الموجود أو بالانقطاعات الحاصلة أحياناً للحواف, بالرغم من عدم وجود مرحلة معالجة مسبقة Pre-Processing ضمن سلسلة الخطوات المتتالية المطبّقة على عدة صور فوق صوتية بأحجام ومصادر مختلفة. ليتم في النهاية حساب القطر الثانوي للقطع الناقص (قطاع رأس الجنين Head) الناتج بالاعتماد على تابع خصائص المنطقة, القياس النهائي يمثّل المسافة بين الجداريين Bi Parietal Diameter BPD, وهو قياس مهم يمكّن الطبيب من تقدير عمر الحمل وتحديد تاريخ الولادة للجنين. تمت مصادقة نتيجة التجزئة بالاعتماد على معايير التشابه, أما دقة القياس النهائي فقد تمت مقارنته مع قياسات يدوية قام بها طبيب مختص. وقد أبدت نتائج المقارنة فعالية الخوارزمية المقترحة ونجاحها بنسبة تصل إلى 98%. This Paper offers an innovative way for auto segmentation of the fetal head in ultrasound US images. There is high amount of noise in US images, which it affects the visual appearance of the area of head. The research depends on auto segmentation mechanism without the need for user intervention at any stage of proposed method, so this is what makes segmentation process is difficult and important at the same, because the weakness of the edges and not fully enclosed in the desired region. We relied on a Level Set method to segment the head area, after determining the initial contour automatically by the Region Properties Function. The proposed method proves effective in the head area segmentation without being influenced by noise or the existence of discontinuities in the edges of the head, despite the absence of a pre-processing stage in a series of steps applied to several ultrasound images in different sizes and sources. The last step is to calculate the secondary diameter of the output ellipse (the fetal head sector) depending on the properties of the region, and this final measurement represents the Bi Parietal Diameter BPD, an important measure enables the physician to assess gestational age and determine the birth of the fetus date. Segmentation result has been authenticated based on similarity criteria, and the final measurement accuracy has been compared with manual measurements carried out by a specialist. The comparison results showed the effectiveness of the proposed algorithm and its success by up to 98%.